2011
DOI: 10.1002/prca.201000121
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress occurs early in Down syndrome pregnancy: A redox proteomics analysis of amniotic fluid

Abstract: Our results indicate that oxidative damage is an early event in the DS pathogenesis and might contribute to the development of deleterious DS phenotypes, including abnormal development and AD-like neuropathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

7
3

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 71 publications
(69 reference statements)
8
74
0
Order By: Relevance
“…By a redox proteomics approach, we identified selective proteins that showed increased oxidation in DS fetuses compared with healthy controls. Our results demonstrated that oxidative stress is an early event in the pathogenesis of DS (147).…”
Section: Down Syndromesupporting
confidence: 59%
“…By a redox proteomics approach, we identified selective proteins that showed increased oxidation in DS fetuses compared with healthy controls. Our results demonstrated that oxidative stress is an early event in the pathogenesis of DS (147).…”
Section: Down Syndromesupporting
confidence: 59%
“…We found increased levels of OS, as indexed by increased protein oxidation, lipid peroxidation, reduction of glutathione and thioredoxin levels and induction of the heat-shock response [19]. Other investigators have also reported increased levels of isoprostanes in second trimester amniotic fluid samples from DS fetuses [20].…”
Section: Is Os the Bridge Between Ds And Alzheimer's Disease?supporting
confidence: 54%
“…Increase in SOD, TBARS and catalase in people with DS supports the use of AO therapy [65]. Increased OS in DS was indicated by rise in protein oxidation and lipid peroxidation with reduction in GSH [66]. The oxidative damage is an early event.…”
Section: Down's Syndrome (Ds)mentioning
confidence: 84%